Effect of Aloe Vera Extract in Inhibit of Candida albicans on Cured Acrylic Resin Plates - Mallombassang, Andi Tenri Biba; Amiruddin, Maqhfirah; Asmah, Nur; Hatta, Mohd (Journal of Syiah Kuala Dentistry Society, 2023)
Introduction: Removable dentures are either whole or partial. Fixed dentures are firmly affixed to the patient's teeth. Dentures reduce functional problems caused by tooth loss, but many individuals don't realize how crucial cleaning them is. Long-term denture use can hinder the tongue and saliva's cleaning of the dental mucosa. Thus, Candida albicans cling better to denture bases and primary agen in candidiasis oral. Aloe vera leaves contain six antimicrobial compounds that prevent the growth of various fungi, bacteria, and viruses, including Candida albicans and Staphylococcus pyogen. Objective: Knowing the effect of aloe vera extract (Aloe vera) with a concentration. Methods: The research method is True Experimental Laboratory, which uses a research design in post-test-only control groups. The Kruskal-Wallis test was used to analyze and interpret the research data results, and the Mann-Whitney U test was used as a follow-up analysis. Results: The normality test results showed a p-value of 0.033 in the control group of aquades smaller than 0.05. This proves that the control equates are generally not distributed because the p-value is smaller than 0.05 (p-value 0. The p-value 0.05 was obtained in the control group, proving that the control group is normally distributed. In the homogeneity test, a p-value of 0.000, smaller than 0.05, is obtained. This proves that the test data results in the control and treatment groups are not homogeneous. Conclus inhibits the development of Candida albicans in heat-cured acrylic resin.